(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article analyzes the possibilities of managing production clusters using artificial intelligence technologies. In the modern economy, artificial intelligence technologies play an important role in optimizing production processes, improving logistics systems, and automating the process of making management decisions. The study studies the theoretical and practical aspects of using artificial intelligence in managing the activities of production clusters, and makes proposals for the development of data-based management mechanisms in the cluster system..